PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN DAN FAKTOR POLITIK TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Organisasi Perangkat Daerah Kota Dumai) - Reni Afriani; Yuneita Yuneita; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study axamines the effect of external pressure, environmental uncertainly, management commitmen dan political factors on the transparency of financial reporting. The population in this research is the organization of dumai city area of 34 opd. Of the existing population then obtained samples in this study as many as 102 respondents. Sampling technique using purposive sampling method, while the data processing method used by SPSS version 20.0 as software to proess data. The results of the research indicate that external pressure has an effect on the transparency of financial reporting with significant value 0,026. Environmental uncertainly has a significant effect of 0,001 on the transparency of financial reporting. Management commitmen has a significant effect of 0,029 on the transparency of financial reporting. And the political factors have a significant effect of 0,012 on the transparency of financial reporting. Keywods : External Pressure, Environmental Uncertainly, Management Commitmen, Political Factors and Transparency of financial reporting.